History of International Relations - Ringmar, Erik (Open textbook library., 2019)
Existing textbooks on international relations treat history in a cursory fashion and perpetuate a Euro-centric perspective. This textbook pioneers a new approach by historicizing the material traditionally taught in International Relations courses, and by explicitly focusing on non-European cases, debates and issues. The volume is divided into three parts. The first part focuses on the international systems that traditionally existed in Europe, East Asia, pre-Columbian Central and South America, Africa and Polynesia. The second part discusses the ways in which these international systems were brought into contact with each other through the agency of Mongols in Central Asia, Arabs in the Mediterranean and the Indian Ocean, Indic and Sinic societies in South East Asia, and the Europeans through their travels and colonial expansion. The concluding section concerns contemporary issues: the processes of decolonization, neo-colonialism and globalization – and their consequences on contemporary society.